Slum Resettlement Along Brantas Riverbanks Case Study at Malang City, East Java - TOMI ADI PURNOMO; HERMAWAN HERMAWAN; IMAM HARDJANTO (Indonesian Journal of Environment and Sustainable Development, 2013)
Urban redevelopment and slum resettlement have become critical issues in many towns in Indonesia. Urban resettlement, however, is one of the most complicated and difficult challenges. Malang City, one of the representative towns in Indonesia tried to displace the slums from the high risk areas along Brantas riverbanks to the RUSUNAWA in 2012. However the result was quite different from the government’s intentions. This study will describe the slums living conditions and analyze their reasons did not leaved high risks zones. The objectives are to understand the dwellers’ incentives to move from the viewpoints of the economy, the living conditions, community ties, and the dwellers’ opportunistic responses. One hundred slum households lived closest to the riverbanks were interviewed. This study revealed that the living conditions in the slums were not necessarily bad and that the slum dwellers had strong economic incentives to continue living there. Nevertheless, they realized that as illegal squatters, they did not have enough incentives to leave from the slums, even with the high risks. Alternative facilities for living and economic activities that could give enough incentives to resettle have not been provided yet by government.   Keywords: RUSUNAWA, high risk zones, slum living conditions, incentives